2022
DOI: 10.1002/saj2.20461
|View full text |Cite
|
Sign up to set email alerts
|

Response of surface soil nutrients and organic carbon fractions to tillage erosion vs. water erosion in an agricultural landscape

Abstract: A mechanistic understanding of nutrient movement associated with the erosion process is required to formulate precision soil conservation measures. We explored the response of surface soil nutrients and soil organic carbon (SOC) fractions to tillage erosion and water erosion. Tillage and water erosion rates were estimated by the directional tillage erosion model and revised universal soil loss equation, respectively. One hundred and twelve surface soil samples (0-20 cm) were collected from a sloping farmland (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Rocci et al (2021) did not find clear effects on the partition of SOC among fractions with an increase in precipitation, although they found a negative tendency for POC and a positive tendency on MAOC. The effect of wind erosion on SOC loss will depend on particle size distribution and soil cover, with vulnerable soils losing 3.6 Mg C ha -erosion depending on hillsope position (Zhao et al, 2022). SOC desestabilization and stabilization processes vary along the hillslope with changes in particle size distribution, degree of weathering, and abundance of secondary minerals (Doetterl et al, 2015a).…”
Section: Vulnerability Of Soc Fractions To Climate Changementioning
confidence: 99%
“…Rocci et al (2021) did not find clear effects on the partition of SOC among fractions with an increase in precipitation, although they found a negative tendency for POC and a positive tendency on MAOC. The effect of wind erosion on SOC loss will depend on particle size distribution and soil cover, with vulnerable soils losing 3.6 Mg C ha -erosion depending on hillsope position (Zhao et al, 2022). SOC desestabilization and stabilization processes vary along the hillslope with changes in particle size distribution, degree of weathering, and abundance of secondary minerals (Doetterl et al, 2015a).…”
Section: Vulnerability Of Soc Fractions To Climate Changementioning
confidence: 99%
“…As the largest and most active carbon pool in the terrestrial ecosystem, soil organic carbon (SOC) plays an important role in maintaining soil fertility and serves as an important factor in judging soil quality, accompanied by an important function in maintaining ecosystem productivity and stability [5]. Studies have shown that SOC usually exists in a combined state of coarse organic matter, fine granular organic matter, and soil minerals, and most of the coarse granular organic matter is concentrated in the soil surface layer and taken away relatively easily by runoffs [6]. As the basic unit of soil structure, soil aggregates are formed by the aggregation, flocculation, and cementation of soil particles [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates oxidation and hydration of the previously protected SOC, enhancing its mineralization (Six et al, 2008; Wang, Cammeraat, et al, 2014). In addition, erosion can preferentially transport finer soil particles together with clay minerals and reactive mineral oxides to colluvial environments (Berhe et al, 2012; Doetterl, Cornelis, et al, 2015; Zhao et al, 2022), providing colluvial soils with increased potential to physico–chemically protect SOC against mineralization. Topography also exerts a control on soil hydrologic conditions via water flow and therefore interacts with mineral weathering and net primary productivity (NPP) (e.g., Metzen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%